Chinese human smuggling organizations: families, social networks and cultural imperatives - Zhang, Sheldon X. (Stanford University Press, 2008)
Coming to America : illegal Chinese migration to the United States -- Becoming a snakehead -- Recruitment, preparation, and departure -- Smuggling activities in transit -- Arrival and payment collection -- Making money from human smuggling -- Organizational and operational characteristics -- The dyadic cartwheel network -- Human smuggling and traditional Chinese organized crime -- Women and Chinese human smuggling -- Future of Chinese human smuggling